Association between trends of mortality and incidence, survival and stage at diagnosis for six digestive and respiratory cancers in United States (2009–2013). Issue 2 (19th July 2022) - Teglia, Federica; Boffetta, Paolo
Abstract : Background: A decrease in cancer mortality has been reported in the USA, possibly due to decreased incidence, downstaging and improved survival. The aim of the present study is to estimate the contribution of these factors on the trend in cancer mortality. Methods: Data on incidence, mortality, stage at diagnosis, and overall and stage-specific survival for six common digestive and respiratory cancers (esophagus, stomach, colorectal, liver, pancreas and lung) during 2009–2013 in the USA from the surveillance, epidemiology and end results (SEER) program, was analyzed using generalized linear models separately among men and women. Results: Our study showed a decrease in mortality for esophageal (−0.09/100 000/year and −0.03/100 000/year), stomach (−0.11/100 000/year and −0.05/100 000/year), colorectal (−0.45/100 000/year and −0.29/100 000/year) and lung cancer (−1.89/100 000/year in men and −0.78/100 000/year in women) in men and women, respectively: for all of them, except lung cancer in women, there was a decrease in the incidence of comparable or greater magnitude; stage distribution and survival also contributed to the decrease in mortality for lung and colorectal cancer. Mortality from pancreatic cancer was stable: an increase in incidence was counterbalanced by an improvement in survival. Mortality from liver cancer increased, driven by an increase in mortality that was not offset by favorable trends in stage distribution and survival. Conclusions: Trends in mortality were primarily affected by changes in incidence; an increase in the proportion of local stage at diagnosis and improved survival, although evident for some cancers, played a lesser role in mortality trends.